The Class A β-Lactamase Produced by Burkholderia Species Compromises the Potency of Tebipenem against a Panel of Isolates from the United States - Scott A. Becka; Elise T. Zeiser; John J. LiPuma; Krisztina M. Papp-Wallace (MDPI AG, 2022)
Tebipenem-pivoxil hydrobromide, an orally bioavailable carbapenem, is currently in clinical development for the treatment of extended-spectrum β-lactamase- and AmpC-producing Enterobacterales. Previously, tebipenem was found to possess antimicrobial activity against the biothreat pathogens, Burkholderia pseudomallei and Burkholderia mallei. Thus, herein, tebipenem was evaluated against a panel of 150 curated strains of Burkholderia cepacia complex (Bcc) and Burkholderia gladioli, pathogens that infect people who are immunocompromised or have cystic fibrosis. Using the provisional susceptibility breakpoint of 0.12 mg/L for tebipenem, 100% of the Bcc and B. gladioli tested as being provisionally resistant to tebipenem. Bcc and B. gladioli possess two inducible chromosomal β-lactamases, PenA and AmpC. Using purified PenA1 and AmpC1, model β-lactamases expressed in Burkholderia multivorans ATCC 17616, PenA1 was found to slowly hydrolyze tebipenem, while AmpC1 was inhibited by tebipenem with a k2/K value of 1.9 ± 0.1 × 103 M−1s−1. In addition, tebipenem was found to be a weak inducer of blaPenA1 expression. The combination of the slow hydrolysis by PenA1 and weak induction of blaPenA1 likely compromises the potency of tebipenem against Bcc and B. gladioli.